KOSOVO THEME IN THE POETRY OF SERBIAN MODERNISTS (Heritage, 2026)
In this paper, we raise the issue of the interpretation of the Kosovo theme in the poetry of Serbian modernists Aleksa Šantić, Jovan Dučić, Milan Rakić, Vladislav Petković-Dis and Sima Pandurović, as well as their companions such as Velimir Rajić, Mirko Korolija and Milutin Bojić. The aim of the paper is to show to what extent the Kosovo theme is developed in all segments of the Kosovo motifs that make up the heroics of the Kosovo myth. The heroics of the Kosovo myth were thematically a national liberation feature. In artistic poetry, the Kosovo theme will grow beyond stylistic trends and eras and will last for centuries, creating a new, artistic Kosovo epic.
Keywords: Kosovo theme, poetry of Serbian modernists, Aleksa Šantić, Jovan Dučić, Milan Rakić, Vladislav Petković-Dis.